Assessment of serum sodium levels in patients of lower respiratory tract infections (LRTI) in children at tertiary care center - Jain, Shruti; Kumar, Vinod; Kapoor, Sangeeta; Bhalke, Santosh; Gupta, Shivanshu (Pediatric Review: International Journal of Pediatric Research, 2019)
Introduction: Lower respiratory tract infection is an infection beneath the larynx which includes: Pneumonia, Wheeze associated Lower respiratory tract infection, Bronchiolitis and Empyema. The aim of this study was to find out the association among hyponatremia and LRTI in tertiary care center. Materials and Methods: The sample size was calculated to be a minimum of 50 subjects. Based on clinical signs and symptoms (as defined by WHO) and infiltrates present on chest X-ray diagnosis of LRTI such as Pneumonia, Bronchiolitis was made. Then patients were subjected to routine investigations such as: Complete blood count, Serum electrolyte (serum sodium) at the time of admission, on day 2 and day 3 by Ion selective electrodes. Results: Mild hyponatremia was found among 11 patients (16.92%), moderate among 9 (13.85%) and severe among 2 (3.08%) patients. Hyponatremia was found to be more common among 1 to 5 years age group as compared to ≥ 2months to 12 months and > 5 to 12 years age groups. Conclusion: Hyponatremia is a significantly common association among hospitalized children with lower respiratory tract infections and it is mainly due to syndrome of inappropriate antidiuretic hormone secretion (SIADH).